THE EFFECT OF THE PEER TUTORING METHOD ON SCIENCE CURRENTS ON THE STUDENTS' LEARNING OUTCOMES IN Vth CLASS SD NEGERI 4 JATIMULYO LAMPUNG SELATAN - Ali Mashari; Putry Agung; Shovira Maulida (SEMAR Journal : Educational Studies, 2022)
The purpose of this study was to determine the effect of the peer tutoring method on the learning outcomes of fifth grade science subjects at SD Negeri 4 Jatimulyo, South Lampung. The method used in this research is quantitative with the type of pre-experimental research one group pretest-posttest design which is used to determine the effect of a treatment on research subjects. The population of this study were all fifth grade students of SD Negeri 4 Jatimulyo, with a sample of the total population. The data from this study were obtained using a multiple choice instrument with 15 questions. The results of this study are quite satisfactory. This can be seen from the results of the posttest score of 2871 which is greater than the total value of the pretest of 2133. The highest posttest score is 100 the highest pretest value is 86. The lowest posttest value is 56, and the lowest pretest value is 26. The total mean posttest is 84.44 pretest 62.73 . That is, the pretest is before the peer tutoring method is implemented and the posttest is after it is implemented. In the calculation of the percentage of 33 students from 34 students, 97% of students have achieved the KKM value from the specified school